2019
DOI: 10.3390/foods8120664
|View full text |Cite
|
Sign up to set email alerts
|

Punica granatum and Citrus spp. Extract Mix Affects Spoilage Microorganisms Growth Rate in Vacuum-Packaged Cooked Sausages Made from Pork Meat, Emmer Wheat (Triticum dicoccum Schübler), Almond (Prunus dulcis Mill.) and Hazelnut (Corylus avellana L.)

Abstract: Sausage made from pork meat, emmer wheat (Triticum dicoccum Schübler), almond (Prunus dulcis Mill.), and hazelnut (Corylus avellana L.) was integrated with a mix of Punica granatum and Citrus spp. extracts to evaluate the possible effects on the growth and oxidation of spoilage microorganisms. Two concentrations of the mix were added, respectively, during sausage-making, and the final products were compared with a control group, without the extract mix, during storage. The use of the mix, especially at 10 g/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 58 publications
(69 reference statements)
6
17
0
Order By: Relevance
“…Hence, this behavior can explain that 2000 ppm and 1000 ppm punicalagin-rich extracts (115.21 mg GAE/g of total phenolic content) have recently shown to reduce by 33% and 22% lipid oxidation, respectively, in sardine oil [29]. Similar results were also obtained by Ranucci et al [30], who also described a reduction of lipid oxidation after the addition of pomegranate and citrus extracts (5 and 10% ) in vacuum-packaged sausages made from pork meat, emmer wheat, almond, and hazelnut.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Hence, this behavior can explain that 2000 ppm and 1000 ppm punicalagin-rich extracts (115.21 mg GAE/g of total phenolic content) have recently shown to reduce by 33% and 22% lipid oxidation, respectively, in sardine oil [29]. Similar results were also obtained by Ranucci et al [30], who also described a reduction of lipid oxidation after the addition of pomegranate and citrus extracts (5 and 10% ) in vacuum-packaged sausages made from pork meat, emmer wheat, almond, and hazelnut.…”
Section: Discussionsupporting
confidence: 78%
“…This antimicrobial activity was also shown in sausages made from pork meat, emmer wheat almond, and hazelnut after addition of pomegranate and citrus extracts (5 and 10% ) [30]. Furthermore, the antimicrobial effect of natural extracts has been previously observed by Del Nobile et al [50], who reported how the inclusion of essential oils of grapefruit (100 ppm) and thymol (110 ppm) kept the microbial quality for 28 days of fish patties.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Differences in TBARS values between BQS and RFBQS samples could be attributed to the degradation of some of these antioxidant compounds during the quinoa processing for the extraction of its fibre-rich fraction. Similar behaviour has been reported in cooked meat products with citrus and pomegranate extracts added, and also, in this case, the antioxidant effect was attributed to the antioxidant compounds (mainly polyphenols) found in these extracts [24]. Although TBARS values were increased during storage time, the amount of malondialdehyde (mg) per kg sample did not exceed the limit for which it could be detected as a rancid taste in sensory analysis for all formulations studied [47].…”
Section: Lipid Oxidationsupporting
confidence: 82%
“…As regards pH values (Table 2), neither the addition of quinoa products nor storage time had any statistically significant effect (p > 0.05) on this parameter. pH values for all sausages may be considered normal for this type of meat product [1,3,24]. Meat product colour is significant to consumer acceptance of products.…”
Section: Physicochemical Analysismentioning
confidence: 99%